2017
DOI: 10.1104/pp.17.00744
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis DNA Methylome Is Stable under Transgenerational Drought Stress

Abstract: Improving the responsiveness, acclimation, and memory of plants to abiotic stress holds substantive potential for improving agriculture. An unresolved question is the involvement of chromatin marks in the memory of agriculturally relevant stresses. Such potential has spurred numerous investigations yielding both promising and conflicting results. Consequently, it remains unclear to what extent robust stress-induced DNA methylation variation can underpin stress memory. Using a slow-onset water deprivation treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 119 publications
(216 reference statements)
6
106
1
Order By: Relevance
“…The potential for DNA methylation to contribute towards plant acclimatory responses, as an “epigenetic” layer regulating the expression of a genotype, remains an enigmatic phenomenon. In contrast to studies that have reported DNA methylation changes associated with abiotic stress (Jiang et al, ; Tricker, Gibbings, Rodríguez López, Hadley, & Wilkinson, ; Wibowo et al, ; Zheng et al, ), we recently reported a lack of drought‐induced methylome variation, persisting in a transgenerational manner, in Arabidopsis (Ganguly, Crisp, Eichten, & Pogson, ). These results of a robust methylome impervious to drought stress raised multiple questions: (a) is robustness a general principle of the methylome or was it specific of drought stress and (b) did the lack of variation in the methylome reflect a lack of physiological memory.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The potential for DNA methylation to contribute towards plant acclimatory responses, as an “epigenetic” layer regulating the expression of a genotype, remains an enigmatic phenomenon. In contrast to studies that have reported DNA methylation changes associated with abiotic stress (Jiang et al, ; Tricker, Gibbings, Rodríguez López, Hadley, & Wilkinson, ; Wibowo et al, ; Zheng et al, ), we recently reported a lack of drought‐induced methylome variation, persisting in a transgenerational manner, in Arabidopsis (Ganguly, Crisp, Eichten, & Pogson, ). These results of a robust methylome impervious to drought stress raised multiple questions: (a) is robustness a general principle of the methylome or was it specific of drought stress and (b) did the lack of variation in the methylome reflect a lack of physiological memory.…”
Section: Introductioncontrasting
confidence: 99%
“…All Arabidopsis plants used in this study were in the Columbia (Col‐0) background and derived from a common inbred parent, to minimize genetic variation and stochastic DNA methylation variation (Crisp et al, ; Ganguly et al, ; Schmitz et al, ). Prior to light, seeds were sown onto moist soil and kept at 4 °C for three nights to allow for seed stratification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we detected an apparent increase in global DNA methylation in the roots of Arabidopsis plants upon Cd exposure (Figures a,b and S1), which is in accordance with the findings of Wang et al (). Several other abiotic stresses, such as salt stress, phosphorus deficiency, and drought stress have also been reported to upregulate DNA methylation in plants (Ganguly, Crisp, Eichten, & Pogson, ; Secco et al, ; Wibowo et al, ). In mammals, the genes involved in the DNA methylation machinery have been linked to Cd‐induced DNA methylation alterations (Benbrahim‐Tallaa, Waterland, Dill, Webber, & Waalkes, ; Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such inherited environmental effects can be transmitted from parent to offspring (and to additional generations in some cases) by diverse and nonmutually exclusive mechanisms, including (a) heritable epigenetic modifications (i.e., DNA methylation marks, histone modifications, and small RNAs) and (b) the allocation of nutritive resources, hormones, mRNAs, and regulatory proteins to seeds or eggs (Herman & Sultan, ; Jablonka, ). As more research has focused on transgenerational plasticity, it has become clear that these effects are highly variable (Colicchio, ; Groot et al., ; Herman & Sultan, ) and nearly absent in some cases (Ganguly, Crisp, Eichten, & Pogson, ). Empirical investigations in diverse plant and animal systems have confirmed that transgenerational environmental effects can be adaptive when parent and progeny environments match (i.e., under positive intergenerational environmental autocorrelations; see, e.g., Bilichak, Ilnystkyy, Hollunder, & Kovalchuk, ; Dantzer et al, ; Herman, Sultan, Horgan‐Kobelski, & Riggs, ; Lopez Sanchez, Stassen, Furci, Smith, & Ton, ; Rasmann et al, ; Slaughter et al, ; Verhoeven & van Gurp, ; Walsh et al, ; Wibowo et al, ).…”
Section: Introductionmentioning
confidence: 99%